Estratégias pedagógicas com uso de tecnologias de informação e comunicação: uma abordagem para a construção do conhecimento em operações aritméticas básicas e nas chamadas "regras de sinais" - Machado, Maurício de Souza (2010)
This piece of work had as aim to verify in which measure a pedagogical strategy with use of several technologies, traditional ones as well as those ones called ICTs, could promote the learning of concepts involved in rule of signs when used with arithmetic operations. The people whom participated of this research were students of a fundamental cycle s recover class with huge cognitive problems, including difficulties with use of basic operations with integers. The methodological approach, in an ample sense, used the principles of Didactic Engineering and qualitative research techniques, as contents analysis, in order to analyze, by Didactic Situations Theory perspective, the protocols produced by students from three research instruments. The interfaces of these instruments were planned to use pencil and paper, calculators and the Geogebra software. The pedagogical strategy adopted allowed to the students understand the rule of signs and the concept of the symmetric of an integer number, using it to improve their own performance related to operations on integer numbers. Moreover, during the investigation, the students could develop the autonomy and the capacity to reflect about the errors made by them, which allowed rebuilding the strategies planned earlier. More than simply provide answers to arithmetic operations, the students could to understand its real meaning